SISTEM PAKAR DIAGNOSA PENYAKIT JANTUNG MENGGUNAKAN METODE CERTAINTY FACTOR BERBASIS WEB - Jadiaman Parhusip; Viktor H. Pranatawijaya; Dwimaryuga Putrisetiani (Seminar Nasional Informatika (SEMNASIF), 2012)
Currently, computers have been widely used in the medical world to help diagnose a disease. The disease is most commonly found is Heart Disease. One technique in the diagnosis of heart disease is an expert system. Expert systems are computer-based system that uses knowledge, facts and reasoning techniques in solving problems that typically can only be solved by an expert in a particular field. Expert system technology provides added value to assist in dealing with an increasingly sophisticated era of information.The method used in software development is the waterfall method. Waterfall method which consists of requirements analysis and definition, software system design, implementation, testing, and maintenance. In a needs analysis and definition, in general this stage to collect all the needs. This need is an early stageor base from the manufacturing process further. Later on in the design of input and output interface is a software system design. Therefore this study aims to develop an expert system used for early diagnosis of heart disease based on symptoms that feel. The system will display the level of trust fowards these symptoms for the possibility of illnesses by patient. The value of trust is the result of calculation using the method of certainty factor (CF). System implementation is realized into the PHP programming language and can be run/ accessed via the web based, which can be accessed at any time by the general public.